Discovery of representatives of the family Nicoletiidae (Insecta: Zygentoma) from caves of Iran, with descriptions of two new supraspecific taxa - Tahami, Mohadeseh Sadat; Molero, Rafael; Gaju, Miquel; Sadeghi, Saber (Zootaxa, 2018)
The first records of the family Nicoletiidae in Iran are given, based on material from subterranean habitats in Fars Province. Two new species are described, one belonging to a new genus of Atelurinae, Persiatelurina farsiana gen. n. sp. n., the other to the genus Lepidospora but representing a new subgenus, Brinckiletinia subgen. n., this new subgenus is close to the subgenus Brinckina, but lacks scales on the thorax. Both new taxa are compared with related species. Nipponatelurina caucasica Kaplin, 2016 is transferred to Persiatelurina caucasica n. comb. The new atelurine was collected in Momtaz and Khan Caves and Lepidospora (Brinckiletinia) malousjanica sp. n. was found in Malousjan Cave. An additional specimen of Lepidospora was collected in Momtaz Cave, and although its specific identity is not clear, it represents a third taxon belonging to the subgenus Brinckina. Data about the habitats of these subterranean Nicoletiidae are presented.